Warfarin doses in the initiation phase among patients with heart valve replacement and atrial fibrillation in Hospital Pulau Pinang - Jia, Teoh Chee (2011)
The use of warfarin is essential in patients having Atrial Fibrillation (AF), Aortic Valve Replacement (AVR) and Mitral Valve Replacement (MVR). However, the use of warfarin may bring major adverse effects such as bleeding and it has dose related side effects. Due to higher incidence of bleeding in initial phase of warfarin therapy and reported fluctuation of dose in initial phase of warfarin therapy after heart valve surgery, this study was conducted to evaluate the changes in warfarin doses among patients after heart valve surgery and atrial fibrillation. All patients having atrial fibrillation, aortic valve replacement and mitral valve replacement who were initiated warfarin therapy in year 2008 till 2010 in Hospital Pulau Pinang was selected as samples. A total of 137 patients were included for this study. Data collected included patient’s age. race, gender, warfarin initiation date, warfarin indication, warfarin dose and INR value for 1st till 12th weeks of warfarin initiation. Statistical analysis was performed using repeated measures ANOVA and repeated measures ANCOVA. Heart valve replacement patients (AVR or MVR) showed increasing trend in warfarin doses during the initial phase of warfarin therapy. This trend was not observed in Al-' patients. The dose of warfarin warfarin initiation for AVR and MVR group (p-value <0.001) but there was no significant difference in AF group. The dose of warfarin was significantly different among AVR and AF patients for first 5 weeks of warfarin initiation. Indications (p-value =0.036) and race (p-value =0.016) were found to be significantly affecting warfarin doses in the initial phase of warfarin therapy but not gender (p-value =0.122) and age (p-value =0.280). Overall, the mean dose of warfarin required was lower compared to western countries. Monitoring should be frequent for patients with heart valve replacement during the initial 3 months period of warfarin therapy.